Predictive value of oxidative, antioxidative, and inflammatory status for left ventricular systolic recovery after percutaneous coronary intervention for ST-segment elevation myocardial infarction - Aksoy,Fatih (2022)
SUMMARY OBJECTIVE: This study aimed to evaluate the association between left ventricular ejection fraction recovery and the total oxidant status, total antioxidant capacity, and high-sensitivity C-reactive protein levels. METHODS: A total of 264 ST-elevation myocardial infarction patients were classified into two groups according to baseline and 6-month follow-up left ventricular systolic function: reduced and recovery systolic function. Predictors of the recovery of left ventricular ejection fraction were determined by multivariate regression analyses. RESULTS: Multivariable analysis indicated that oxidative status index, baseline left ventricular ejection fraction and peak creatine-kinase myocardial bundle level, and high-sensitivity C-reactive protein were independently associated with the decreased of left ventricular ejection fraction at 6-month follow-up. CONCLUSION: Oxidative stress and inflammation parameters were detrimental to the recovery of left ventricular ejection fraction in patients with ST-elevation myocardial infarction.